Post-discharge Mortality in Patients With Delirium and Dementia: A 3-Year Follow Up Study - Schnorr, Thiemo; Fleiner, Tim; Schroeder, Henning; Reupke, Ira; Woringen, Frank; Trumpf, Rieke; Schroeder, Stefan; Zijlstra, Wiebren; Haussermann, Peter (Frontiers in Psychiatry, 2022)
Background: Delirium and dementia are prominent psychiatric diseases in old age and connected with poor outcomes for people affected. Nevertheless, there is a lack of knowledge concerning the long-term prognosis of patients with dementia and delirium. This study analyzes mortality, readmission rates and discharge destinations of patients with dementia or delirium superimposed on dementia (DSD) within three years after discharge from hospital. Methods: A Cross-sectional, monocentric cohort study was conducted at the department of geriatric psychiatry of the LVR hospital cologne, using structured telephone interviews and analyses from the clinical information system. All patients with dementia and DSD, admitted between December 2014 and November 2015, were screened for eligibility. Results: In total, 113 patients were included, 49 patients with dementia (M 80 years, female 49%) and 64 with DSD (M 82 years, female 47%). Three years after discharge, 66 patients (58%) had died (95% CI 91.9–112.5; p=.53). Within the first three months, 9 patients (14%) with DSD deceased, but no patient from the dementia group (95% CI 11.3–12.7; p=.01). Out of all patients, 17 patients were readmitted and nursing homes were the predominant discharge destination (55%). Conclusions: This analysis revealed a high post-discharge mortality rate of patients with dementia and DSD. For patients with DSD, a close clinical monitoring, mainly within the first three months after discharge, should challenge the significantly increased acute-mortality. These findings should set the pattern for a comprehensive analysis of long-term effects of dementia and DSD. More studies are required for better understanding and comparability in this field of research and healthcare.